Exploration of clinicians' perspectives of using a bereavement risk screening tool in a palliative care setting: a qualitative study. Issue 3 (1st September 2020) - Lawler, Lois; Noble, Christy; Plunkett, Emily; Wenke, Rachel; Johns, Lise
Abstract: To minimise the adverse outcomes of prolonged complex bereavement, health professionals need effective risk screening tools to identify those at risk. However, existing tools can be challenging to implement in the clinical setting. This qualitative study aimed to explore clinicians' perspectives and experiences of using the Bereavement Risk Index (BRI) screening tool, including identifying barriers and enablers regarding its use and what they perceived as important domains in bereavement risk screening. Data was collected through semi-structured group and individual interviews and deductively analysed using the Theoretical Domains Framework. Eleven participants employed in one regional palliative care service were interviewed. The results revealed three key implications: 1) a risk screening tool is highly beneficial, however contextual factors can limit its implementation; 2) clinician confidence in the tool and perception of the tool's comprehensiveness are significant factors in its use; 3) feedback is needed as to whether clinicians' assessment of bereavement risk remains accurate and valid in the longer term.